HIDROPONIK MENUJU KETAHANAN PANGAN KELUARGA DALAM MEMBENTUK PERTANIAN KUAT DAN TERPADU - Istiyono, Yogi Priyo; Sumatirta, Edi Sumatirta; Triyanto, Irfan Rusydi; Abdillah, Irsyad Thalib; Dibyantoro, Dibyantoro; Putri, Widya (LPPM Universitas Bina Bangsa, 2024)
Hydroponics is one alternative that can be used to increase plant productivity on narrow land. With the advancement of agricultural technology, it is possible to plant vegetables out of season. For this reason, a green house is used and is generally carried out with a hydroponic system, so that the need for vegetables can be met and its continuity can be better maintained. Hydroponics is a term used to explain how to grow crops without using soil as a planning mendium. The use of inorganic pesticides can contaminate plant tissue wich will also have an impact on consumers. With the many advantages of hydroponic technology and the increasing need for vegetable commodities, there are business opportunities in agriculture with a hydroponic system that has promosing prospects. Hydroponic systems are divided into three, namely substrate hydroponics, NFT (Nutrient Film Technique), and aeroponics. However, the substrate and NFT hydroponic systems are the most widely developed. In its development, it is not only for a small scale but also includes a large or commercial scale. This community service activity is carried out in several stages. How to plant hydroponic plants to increase family food security